Polemik Sengketa Hak Atas Tanah - Muh. Rizal Ramli; Kairuddin Karim; Muhammad Akbar Fhad Syahril (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2021)
The emergence of various problems regarding land proves that the use, control, and ownership of land in our country has not been orderly and orderly. This research aims to find out the process of resolving land rights disputes in Sidenreng Rappang district. This research uses normative research types supported by the case study approach, the analytical approach. Analysis of legal materials in this study uses deductive logic reasoning. Normative legal research uses logical and prescriptive analysis and argumentation. Normative legal research is generally qualitative. The results showed the process of resolving land disputes in the Court Sidenreng Rappang, more litigation, as in the case with case number: 18 / Pdt.G / 2020 / PN Sdr with various stages until the cancellation in the previous decision.